The emerging potential of siRNA nanotherapeutics in treatment of arthritis - Anjali Kumari; Amanpreet Kaur; Geeta Aggarwal (Elsevier, 2023)
RNA interference (RNAi) using small interfering RNA (siRNA) has shown potential as a therapeutic option for the treatment of arthritis by silencing specific genes. However, siRNA delivery faces several challenges, including stability, targeting, off-target effects, endosomal escape, immune response activation, intravascular degradation, and renal clearance. A variety of nanotherapeutics like lipidic nanoparticles, liposomes, polymeric nanoparticles, and solid lipid nanoparticles have been developed to improve siRNA cellular uptake, protect it from degradation, and enhance its therapeutic efficacy. Researchers are also investigating chemical modifications and bioconjugation to reduce its immunogenicity. This review discusses the potential of siRNA nanotherapeutics as a therapeutic option for various immune-mediated diseases, including rheumatoid arthritis, osteoarthritis, etc. siRNA nanotherapeutics have shown an upsurge of interest and the future looks promising for such interdisciplinary approach-based modalities that combine the principles of molecular biology, nanotechnology, and formulation sciences.